FROM PICTOGRAPHY TO ALPHABET; THE EVOLUTION OF THE WRITING SYSTEM (Multidisciplinary Journal of Science and Technology, 2026)
The article is dedicated to the history of the origin and development of writing, which is a fundamental component of humanity's cultural heritage. It reveals the path from the simplest and most visual form of writing—pictography—through complex systems (ideograms, syllabograms) to the invention of the alphabet based on the phonetic principle. This process is illustrated by the example of the development and improvement of writing systems in various ancient civilizations: Mesopotamia, Egypt, China, Phoenicia, and Greece.